Facile synthesis of (Z)-anti-homoallylic alcohols from 3-(pinacolatoboryl)allyl alcohols, aldehydes, and triorganoboranes via a palladium-catalyzed three-component reaction. Issue 31 (3rd August 2016) - Horino, Yoshikazu; Aimono, Ataru; Minoshima, Naoki; Abe, Hitoshi
Graphical abstract: Highlights: Allylic alcohols can be utilized directly as an allylating agent. ( Z )- anti -Homoallylic alcohols can be readily synthesized. Triorganoboranes are used as a coupling reagent. Pd/R3 B induces the formation of π-allylpalladium species from allylic alcohols. Abstract: A palladium-catalyzed three-component reaction of 3-(pinacolatoboryl)allyl alcohols, aldehydes, and triorganoboranes was developed. The present protocol provides facile access to synthetically useful ( Z )- anti -homoallylic alcohols with high diastereoselectivity and high levels of alkene stereocontrol. Furthermore, single-flask reaction sequences to synthesize ( Z )- anti -homoallylic alcohols starting from propargyl alcohols by using palladium-catalyzed three-component reaction are successfully achieved.